Brown child the best of the Faigao poetry and fiction, 1984-2012 - Kintanar-Alburo, Erlinda; Yu, Hope Sabanpan (Cebu City University of San Carlos Press and Cebuano Studies Center, 2013)
Collection of Cebuano poetry and fiction from the Cornelio Faigao Memorial Annual Writers workshops from 1984 to 2012.
English and Cebuano.
Keywords: Philippine literature (English).; Cebuano poetry; Cebuano fiction